Asymptomatic RT-PCR positive COVID-19 patients in orthopaedic pre-operative evaluation during the peak of the second wave. (January 2022) - Samiul Islam, Md.; Parvin, Sultana; Mahbubur Rahman Khan, Mohammad; Jahangir Hossain, G.M.; Zahiruddin, A.K.M.; Jahangir Alam, Md; Hossen, Monaim; Wahidur Rahman, Md; Shahidul Islam, Syed; Abdul Gani Mollah, Md
Highlights: The detected asymptomatic COVID-19 infection rate during the peak of the second wave among the pre-operative orthopaedic patients was 12.3%. Younger age, female gender, longer duration of admission to RT-PCR test interval, and thereby long hospital stay were found to be risk factors for asymptomatic RT-PCR to be positive. Further, additional investigations focused on at-risk individuals may be useful in identifying asymptomatic cases that could be missed by RT-PCR evaluation. We are in the opinion of doing RT-PCR evaluation in orthopaedic pre-operative patients before elective surgery. Abstract: Introduction: Asymptomatic COVID-19 patients are the most challenging and feared obstacles in resuming these surgical procedures. The purpose of this study was to evaluate the proportion of asymptomatic carriers detected by RT-PCR in pre-operative orthopaedic evaluation during the peak of the second wave. Methods: 514 asymptomtomatic COVID-19 patients, negative for TOCC (Travel, Profession, Cluster, Contact) risk factors were observed retrospectively. A nasopharyFngeal RT-PCR test was obtained 48 to 72 h before the surgery in all cases. Possible risk factors for a positive test was identified. Results: The detected asymptomatic COVID-19 infection rate during the peak of the second wave among the pre-operative orthopaedic patients was 12.3%. Younger age, female gender, longer duration of admission to RT-PCR test interval were found to be significant (p= < 0.05) risk factors for asymptomatic RT-PCR to be positive. The hazard ratio (HR) for being asymptomatic RT-PCR positive was 4.3 (p = 0. 025), while the RT-PCR was performed at 14 days, but the HR increased to 9.2 (p = 0.049) when the test was performed after 45 days. Conclusion: According to our findings, pre-operative testing to rule out COVID-19 should be regarded as a critical step in preventing the disease clusters in hospitals.